Ionic Cards : A Multipurpose Game to Study Ionic Formula in Chemistry - Stanley, Theresa (Multidisciplinary Applied Research and Innovation, 2022)
The traditional teaching of ionic formulas in Chemistry is insufficient for students to grasp the concept of ionic Formulas. Formula writing needs practice and understanding if a student wants to get the idea. In today’s education, it is emphasised that students should be engaged collaboratively in the learning process, while teachers should serve as guides for the students. In this quantitative research, a proposed game- based learning approach is the collaborative learning process of ionic formula writing. The card comprises 26 round cards made of thin woods with two different colours to differentiate the positive and negative ions. Using the ionic cards in formula writing by 37 form four secondary school students in Cheras found that card games positively affect perceived learning effectiveness and Satisfaction. There is also an association between learning effectiveness and satisfaction. The game will start with students playing the memory game to test their understanding of the 26 ionic in their chemistry syllabus. Once the students have mastered the name of all 26 ions, they will move to the second phase of the game, formula building, and finally, calculation of the Molar Mass. Students will incorporate mathematics in this game-based learning, where they will calculate the molar mass of the ionic compound. The ionic card is in a dual language of Bahasa Melayu and English, making it a multilingual card game besides being a multipurpose card game.